Grafting effectiveness of Anadara granosa shell combined with sardinella longiseps gel on the number of osteoblast-osteoclast cells - Eddy Hermanto; Rima Parwati Sari; Asri Cahyadita Dwi Imaniar; Kevin Anggoro (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Bone grafts derived from Anadara granosa shells contain calcium carbonate that possesses bone-healing properties. The combination of Sardinella Longiceps fish oil, containing EPA and DHA, and Anadara granosa shells was assumed to regulate the number of osteoblasts-osteoclasts during the bone-healing process. Purpose: This study aimed to determine the effectiveness of Anadara granosa shell grafts, combined with Sardinella Longiceps fish oil, in the bone-healing process by observing the ratio of osteoblasts-osteoclasts in Rattus novergicus rats. Methods: The Wistar rat subjects (n = 25) were divided into five groups, namely: one untreated group (control), one group treated with bone grafts derived from Anadara granosa shells (P1), and the other three groups treated with a combination of Anadara granosa shells and Sardinella longiceps fish oil at concentrations of 10%, 20%, and 30% (P2, P3, and P4). Then, a wound equivalent in size to half the diameter of a round bur (±1.5mm) was intentionally inflicted on the right femur of all the subjects. The rats were subsequently sacrificed on day 14, their femur in the transversal side being cut before HE staining was completed. Thereafter, the ratio of osteoblasts to osteoclasts was measured by means of a light microscopy. The data was subsequently analyzed using one-way ANOVA. Results: The average number of osteoblasts in all research groups increased, viz: 9.420±0.8044 for control group (K), 12.080±0.79811 for group P1, 20.020±0.7190 for group P2, 25.940±0.7197 for group P3, and 36.280±0.9985 for group P4. Similarly, the number of osteoclasts in all groups subject to analysis also increased, namely: 1.73±0.098 for group K, 2.19±0.305 for group P1, 1.60±0.088 for group P2, 1.60±0.724 for group P3, and 1.80±1.302 for group P4. Moreover, the results of the One-way Anova test confirmed that there were no significant differences in osteoclasts between all research groups (p>0.05). The results of the one-way ANOVA and LSD tests confirmed there to be significant differences (p <0.05) between group K and other treatment groups (P1, P2, P3, and P4). Conclusion: The grafts derived from the combination of Anadara granosa shells and Sardinella longiceps gel can induce the production of osteoblasts, but not in the numbers necessary during the healing processin the femurs in Rattus novergicus rats.